Research on Parameter Design and Control Strategy of Bidirectional CLLC Resonant Converter - Ding, Huachen; Zhu, Jie; Yuan, Haohui (International Journal of Electric Power and Energy Studies, 2026)
Under the context of energy structure transition and rapid advancement in power electronics, DC-DC converters, as key interface circuits for efficient power conversion and stable power supply, have become core components in modern power systems. Among various DC-DC converter topologies, the CLLC resonant converter features high power density and excellent galvanic isolation. Its topology typically integrates a high-frequency transformer for energy transfer, which not only provides electrical isolation between input and output but also reduces the size of magnetic components by increasing the switching frequency, thereby enhancing system power density. However, parameter design of the CLLC resonant converter remains challenging, requiring a trade-off between gain flatness and soft-switching range in bidirectional operation, coordination of the complex coupling among multiple resonant elements and parasitic parameters, and satisfaction of frequency regulation and efficiency optimization under wide input/output voltage ranges-constraints that are numerous and mutually restrictive. During the control process, the system suffers from long settling time and slow dynamic response. To address these issues, this paper first introduces the topology of the CLLC resonant converter. In view of the difficulties in parameter design, the fundamental harmonic analysis (FHA) method is adopted to design the parameters of the CLLC resonant converter. Combined with the control strategy, a prototype design method for the CLLC converter is completed.